Diagnostic Investigation of 100 Cases of Abortion in Sheep in Uruguay: 2015–2021 - Dorsch, Matías A.; Francia, María E.; Tana, Leandro R.; González, Fabiana C.; Cabrera, Andrés; Calleros, Lucía; Sanguinetti, Margarita; Barcellos, Maila; Zarantonelli, Leticia; Ciuffo, Camila; Maya, Leticia; Castells, Matías; et al. (Frontiers in Veterinary Science, 2022)
The aim of this work was to identify causes of abortion through laboratory investigations in sheep flocks in Uruguay. One hundred cases of abortion, comprising 58 fetuses, 36 fetuses with their placentas, and 6 placentas were investigated in 2015-2021. Cases were subjected to gross and microscopic pathologic examinations, and microbiological and serological testing for the identification of causes of abortion, including protozoal, bacterial, and viral pathogens. An etiologic diagnosis was determined in 46 (46%) cases, including 33 (33%) cases caused by infectious pathogens, as determined by the detection of a pathogen along with the identification of fetoplacental lesions attributable to the detected pathogen. Twenty-seven cases (27%) were caused by Toxoplasma gondii, 5 (5%) by Campylobacter fetus subspecies fetus, and 1 (1%) by an unidentified species of Campylobacter. Fourteen cases (14%) had inflammatory and/or necrotizing fetoplacental lesions compatible with an infectious etiology. Although the cause for these lesions was not clearly identified, T. gondii was detected in 4 of these cases, opportunistic bacteria (Bacillus licheniformis, Streptococcus sp.) were isolated in 2 cases, and bovine viral diarrhea virus 1 subtype i (BVDV-1i) was detected in another. Campylobacter jejuni was identified in 1 (1%) severely autolyzed, mummified fetus. BVDV-2b was identified incidentally in one fetus with an etiologic diagnosis of toxoplasmosis. Microscopic agglutination test revealed antibodies against ≥1 Leptospira serovars in 15/63 (23.8%) fetuses; however, Leptospira was not identified by a combination of qPCR, culture, fluorescent antibody testing nor immunohistochemistry. Neospora caninum, Chlamydia abortus, Chlamydia pecorum, Coxiella burnetii and border disease virus were not detected in any of the analyzed cases. Death was attributed to dystocia in 13 (13%) fetuses delivered by 8 sheep, mostly from one highly prolific flock. Congenital malformations including inferior prognathism, a focal hepatic cyst, and enterohepatic agenesis were identified in one fetus each, the latter being the only one considered incompatible with postnatal life. Toxoplasmosis, campylobacteriosis and dystocia were the main identified causes of fetal losses. Despite the relatively low overall success rate in establishing an etiologic diagnosis, a systematic laboratory workup in cases of abortion is of value to identify their causes and enables zoonotic pathogens surveillance.